‘Cure’ as the gold standard for likelihood ratio assessment: theoretical considerations - Rutten, A.L.B; Stolper, C.F; Lugten, R.F.G; Barthels, R.W.J.M (Homeopathy, 2004)
A gold standard is necessary to assess the validity of homeopathic symptoms. The gold standard is ‘cure’, but this is difficult to define, and depends on consensus. The likelihood ratio (LR) method will give valid results only if the gold standard is reliable. False positives (patients incorrectly classified as cured) weaken results of LR investigation. Weakening the standard to enlarge the research population will seriously bias the results. The same gold standard should be used in LR assessment of all symptoms.
Keywords: likelihood ratio; Bayesian analysis; gold standard; cure; consensus